Flora of Bahia: Leguminosae – Centrosema (Papilionoideae: Phaseoleae) - Barreto, Kamilla Lopes; Fernandes, Moabe Ferreira; de Queiroz, Luciano Paganucci (SITIENTIBUS série Ciências Biológicas, 2020)
The taxonomic treatment of Centrosema (Leguminosae) from the State of Bahia, Brazil, is presented. Fifteen species are recognized, which represents 50% of the Centrosema species recorded in Brazil. The treatment includes keys to identification, descriptions, illustrations, general notes and geographic distribution maps for the species in Bahia.